SOLID DOMESTIC WASTE MANAGEMENT AS RESULT OF BALANCED PUBLIC ADMINISTRATION - Radkova O.S. (Pressing Problems of Public Administration, 2018)
The article is devoted to the problem issues of solid domestic waste management in the conditions of the modern Ukraine. The state of public administration is analyzed, and solid domestic waste management problems are suggested to be solved by coordination of environmental, economic and social interests of the authorities, economic entities, and the population.